O Congresso Nacional, as relações civis-militares e a política de defesa no Brasil (1999-2014) - Madruga, Florian Augusto de Abreu Coutinho (2015)
After 2008, Brazil implemented a series of unprecedented actions in the field of defense policies since the country became a democratic nation once again. The publishing of the National Defense Strategy was a milestone in this process. This document allowed for reforms at the Ministry of Defense and the expansion of strategic projects to reequip the Armed Forces. For the first time, investments were higher than all expenditures stipulated in the national budget meant for defense. In addition, the military expanded their social services in the Amazon and participated more actively in public security actions in Brazilian cities. The main objective of this paper is to assess how this new conjuncture affected the parliamentary activities related to our national defense and military matters. In order to achieve this, a survey of all propositions made by congressional representatives and senators regarding this topic since 1999 – year in which the Ministry of Defense was created – was carried out. The results obtained show that defense policies continue having a secondary role at the National Congress. Despite the implementation of parliamentary fronts, subcommittees and the use of other innovative instruments that increased the visibility of this topic in both legislative houses, the number of legislative initiatives diminished in the last few years. On the other hand, control, monitoring and investigation institutions, such as the Public Prosecution Service (Ministério Público) and the Brazilian Audit Court (TCU), have been more active. Furthermore, we observed that the most active representatives come from states that have a higher number of military personnel when compared to the number of inhabitants. This suggests an electoral connection in the work related to defense issues.